Body trust in Korean population: validation of the Korean version of the body trust scale - Oh, Yunyoung; Seo, Jang-Won (Frontiers in Psychiatry, 2025)
BackgroundInteroception is the ability to perceive and integrate internal sensations. A key component of interoception, body trust, involves trusting internal sensations in daily life and feeling safe within one’s own body. Problems in body trust are linked to psychological disorders, including eating disorders and suicidal behaviors. However, existing tools for measuring body trust have several limitations, and the most recently developed promising instrument to address these issues is the Body Trust Scale (BTS). This study aimed to validate the Korean version of the BTS in a sample of Korean adults.MethodsA total of 775 participants completed the BTS and other measures of positive body image, interoceptive sensibility, body investment, eating pathology, visceral sensitivity, self-harm behaviors, and suicidal ideation. The reliability, factor structure, invariance across age groups and gender, convergent validity, and discriminant validity of the BTS were examined.ResultsResults revealed that the Korean version of BTS has a three-factor structure consistent with the original scale. It also demonstrated good internal consistency, as well as convergent and discriminant validity. Partial scalar invariance across age groups and full measurement invariance across gender were also established.ConclusionThe Korean version of the BTS is a reliable and valid instrument for measuring body trust in Korean adults. It is expected to have clinical utility for assessing body trust, with a specific focus on eating pathology and suicide risk.